(untitled) - Tsuda, Noritake (Tokyo, 1935)
Japanese Art offers readers a comprehensive view of Japanese art through Japanese eyes—a view that is the most revealing of all perspectives. At the same time, it provides readers with a guide to the places in Japan where the best and most representative creations of Japanese art are to be seen.
Keywords: Nghệ thuật,Art; Nhật Bản,Japan